Prose Literature as a Means of Expressing African Culture a Study of Chinua Achebes Things Fall Apart - Nkechinyere, Eze Mabel; Nonye, Nnani Henrietta (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study examines prose literature as a means of expressing, African culture as presented in Buchi Emecheta’s “The joys of motherhood and Chinua Achebe’s Things fall apart respectively. The researcher looked at the history of African culture in Nigeria. A number of critical essays in which some of the realities that portray African culture were reviewed. It came to lime light that there is African culture among Africans as opposed to the notion being portrayed to the outside world by the Europeans. The conclusion is that these works, Things fall apart and The joys of motherhood continue to be a demonstration to show that there is an African culture. This is the main outlook of the novels in this research.